Urban consolidation, power relations, and dilapidated residential redevelopment in Mutoulong, Shenzhen, China. (October 2019) - Li, Xiang; Han, Sun Sheng; Wu, Hao
Recent policy initiatives for urban development have changed the relationships among stakeholders in China's urban consolidation processes. Building upon Giddens' (Giddens A (1984) The Constitution of Society: Outline of the Theory of Structuration . Berkeley, CA: University of California Press.) structuration theory and Ostrom's (Ostrom E (2005) Understanding Institutional Diversity . Princeton, NJ: Princeton University Press) institutional analysis and development thesis, this paper develops a power arena analytic framework, and uses it to examine the new power relations among the stakeholders in a dilapidated residential redevelopment project in Shenzhen. Our findings reveal that Shenzhen's new approach incentivised the developer to frame a local decision-making structure which aligned the property owners into two broad groups: those who supported the developer, or cooperative, and those who disputed with the developer, or un-cooperative . Shenzhen's new attempt was unable to balance power distribution between the main stakeholders and caused intense conflicts and poor project outcomes. A range of factors, including passive participation of residents in project preparation, weak mechanisms to curb speculation, and policy inconsistency associated with tiers of governments, were responsible for the poor performance. These findings contribute to the understanding of the complexity in power relations underlying urban development influenced by planning policy.